Measuring the efficiency and productivity of agricultural cooperatives - Pokharel, Krishna Prasad (Kansas State University, 2016)
This dissertation focuses on measuring the efficiency and productivity for agricultural cooperatives in the United States using the data envelopment analysis (DEA) approach. Economic measures such as cost efficiency, economies of scale, and economies of scope are measured by estimating a cost frontier in a multiproduct framework. Productivity growth is measured using the biennial Malmquist index approach. The cost frontier is the basis for calculating cost efficiency, economies of scale, and economies of scope as the cost frontier estimation in a multiproduct approach describes how cost changes as output changes. The estimates of economies of scale and scope have important implications for agricultural cooperatives because most of the cooperatives sell more than one product. Understanding the impact of changing output levels or mixes on the cost structure is helpful to improve the performance of cooperatives. Further, scope economies estimate the percentage of cost savings through product diversification in a multiproduct firm. The trade-off between cost efficiency and multiproduct scale economies allows the estimation of whether a higher percentage of cost can be eliminated by becoming cost efficient or changing the scale of operations. The economic measures are estimated using a single cost frontier (multi-year frontier) and annual cost frontiers. Multiproduct economies of scale and economies of scope exist indicating that increasing scale and product diversification can reduce cost for agricultural cooperatives. The mean values of product-specific economies of scale for all outputs are close to one indicating that cooperatives are operating close to constant returns to scale. The comparison between cost efficiency and scale economies suggests that smaller cooperatives can save a higher percentage of cost by increasing the scale of operations rather than just becoming cost efficient. Because larger incentives exist for small cooperatives to increase scale, mergers will likely continue until economies of scale are exhausted in the industry. Annual estimates show that agricultural cooperatives have become less cost efficient over time, but economies of scale and economies of scope remain consistent across years. Many agricultural cooperatives face economies of scale indicating that variable returns to scale as opposed to constant returns to scale is the appropriate technology for modeling agricultural farm marketing and supply cooperatives. Further, the Kolmogorov-Smirnov (KS) test and two sample t-test are used to examine whether economic measures estimated from a single frontier and annual frontiers are statistically different. The KS test and t-test indicate that economic measures obtained from the single frontier are statistically different from those measures calculated from annual frontiers. This indicates that the cost frontier has shifted over time. Productivity growth of agricultural cooperatives is estimated using the biennial Malmquist productivity index (BMI) under variable returns to scale over the period 2005 to 2014. The BMI avoids numerical infeasibilities under variable returns to scale compared to traditional methods. The BMI is decomposed into efficiency change and technical change to evaluate the sources of productivity growth. Overall, agricultural cooperatives gained 34% cumulative productivity growth during the decade allocated by -2% and 37% cumulative technical efficiency change and technical change over the study period. Technical change was the major source of productivity growth rather than efficiency change. Cooperatives can achieve higher productivity by increasing managerial efficiency and by investing in technology.
Keywords: Efficiency; Productivity; Nonparametric Approach; Malmquist Index; Agricultural Cooperatives